A prospective observational study to evaluate prevalence of asymptomatic bacteriuria in pregnancy - Shirsage, Maheshwari; G., Rajeshwari; Prabhudev, Prema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Asymptomatic bacteriuria is under-diagnosed condition in pregnancy. Prompt recognition of asymptomatic bacteriuria and its treatment is necessary as this condition can be associated with adverse maternal and foetal complications. Screening of asymptomatic bacteriuria is easy and replicable and goes a long way in promoting safer maternal and foetal outcomes. The aim of the study was to determine (a) prevalence of asymptomatic bacteriuria in pregnant women attending antenatal care and determine its association with age, parity and socio-economic status, and (b) microbiological patterns of the causative organism. Methods: This was a prospective, observational study that evaluated 200 pregnant women visiting antenatal care in tertiary care hospital, SS Institute of Medical Sciences and Research Centre, Davangere, India. A study was conducted in Department of Obstetrics and Gynecology. Subjects having fever, symptoms of urinary tract infection, underlying co-morbid conditions were excluded from the study. Those willing to give a valid consent with no signs of urinary tract infection were included in the study. Results: The prevalence of asymptomatic bacteriuria was noted to be 19% in our study. The most common organism noted to cause asymptomatic bacteriuria was noted to be E. coli followed by Staphylococcus aureus. The prevalence of asymptomatic bacteriuria was noted to be highest in the second trimester followed by those in first trimester. Conclusions: Asymptomatic bacteriuria is widely prevalent in pregnancy. Pregnant women should be screened every trimester for presence of asymptomatic bacteriuria.